Maternal-child health in Pelotas, Rio Grande do Sul State, Brazil: major conclusions from comparisons of the 1982, 1993, and 2004 birth cohorts Saúde materno-infantil em Pelotas, Rio Grande do Sul, Brasil: principais conclusões das comparações de coortes de nascimento de 1982, 1993 e 2004 - Fernando C. Barros; Cesar G. Victora (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
Important changes were observed in maternal characteristics, health care indicators, and child health during the 22 years covered by the three population-based birth cohort studies conducted in the city of Pelotas, Southern Brazil. Maternal education levels improved, cigarette smoking during pregnancy was reduced, and birth intervals became longer. Also, there were more single mothers, and maternal obesity increased. Coverage of antenatal and delivery care by professionals improved, but inductions and caesarean sections increased markedly, the latter accounting for 45% of deliveries in 2004. With regard to child health, the reductions in neonatal and infant mortality rates were modest, and the significant increase in preterm births - 14.7% of all births in 2004 - appears to have colluded with this stagnation. Other infant health indicators, such as immunization coverage and breastfeeding duration, showed improvements over the period. Regarding infant nutrition, malnourishment at age 12 months decreased, but the prevalence of overweight was higher in 2004. The existence of three population-based birth cohorts using comparable methodology allowed for the study of important secular trends in maternal and child health. Foram observadas mudanças importantes nas características maternas, de assistência à saúde e de saúde infantil ao longo dos 22 anos cobertos pelas três coortes de base populacional na cidade de Pelotas, Rio Grande do Sul. Melhorou o nível de escolaridade materna, houve uma redução no tabagismo durante a gravidez e aumentou o espaçamento entre filhos. Além disso, havia mais mães solteiras e aumentou a obesidade materna. Melhoraram a cobertura pré-natal e assistência ao parto por profissionais, mas houve um aumento marcante nos partos induzidos e nas cesarianas, que representaram 45% do total de partos em 2004. Com relação à saúde infantil, houve uma redução apenas modesta nas taxas de mortalidade neonatal e infantil, e o aumento significativo nos partos prematuros (14,7% de todos os nascimentos em 2004) parece haver contribuído para essa estagnação. Outros indicadores de saúde infantil, como cobertura de imunização e duração do aleitamento materno, melhoraram durante o período. Em relação à nutrição infantil, a desnutrição aos 12 meses de idade diminuiu, mas a prevalência de sobrepeso foi maior em 2004. A existência de três coortes de nascimento de base populacional utilizando metodologias comparáveis permitiu o estudo de importantes tendências seculares na saúde materno-infantil.